2007
DOI: 10.1111/j.1399-0012.2007.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptom experience after lung transplantation: impact on quality of life and adherence

Abstract: This study establishes a relationship between patients' perceptions of immunosuppression-related symptom experiences and the impact on QoL and adherence. Immunosuppression is accompanied by significant adverse effects in both symptom frequency and distress. Most frequently experienced symptoms do not necessarily have the greatest impact on perceived distress, and vice versa. High levels of adverse effects tend to negatively influence patients' QoL and adherence. Future research is required to understand the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 28 publications
6
85
1
Order By: Relevance
“…Although HRQoL in transplant recipients has been extensively assessed, a systematic approach to incorporate symptoms and the impact of immunosuppressionrelated side-effects into HRQoL research is rarely documented [14][15][16]. The concept refers to a physical, psychological/ mental, and social domain related to the patients' health status for a defined period of time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although HRQoL in transplant recipients has been extensively assessed, a systematic approach to incorporate symptoms and the impact of immunosuppressionrelated side-effects into HRQoL research is rarely documented [14][15][16]. The concept refers to a physical, psychological/ mental, and social domain related to the patients' health status for a defined period of time.…”
Section: Introductionmentioning
confidence: 99%
“…High level of symptom distress may lead to nonadherence, to reduced HRQoL, and subsequently to decreased graft survival [10][11][12]. Careful assessment and management of symptom experiences, therefore, is critical to providing patients with the best possible outcomes and quality of life for the long-term following solid organ transplantation [3,4,6,8,9,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical outcomes and HRQoL: BOS versus comorbidities versus others Several longitudinal studies have shown that lung transplantation improves QoL post-transplant for many patients [353][354][355][356][357][358]. Anecdotally, this is not surprising given the precarious prognosis and QoL status of patients awaiting LTx almost by definition and the injection of hope and improved functional status that usually occurs once the operative ''hurdle'' of a lung transplant procedure has been passed.…”
Section: Measuring Qolmentioning
confidence: 99%
“…13,14 Lung recipients are also likely to postpone, skip, or reduce doses of immunosuppressive medication. 15 Published studies with patients have demonstrated how posttransplant computer-based education strategies and home monitoring education can increase adherence to overall posttransplant home care regimen, 16,17 taking immunosuppressant medications, 18 performing spirometry, 16,17,19 and checking for signs of skin cancer. 20,21 To date, however, research exploring the entire range of education needed for lung patients, especially before transplant, has been neglected.…”
mentioning
confidence: 99%